Maximizing the utilization of Calcium species in the supercages of CaNa-FAU zeolite for efficient CO2 capture - Sun, Xinyu; Zhang, Quanqi; Li, Sihan; Zhang, Yiming; Liu, Meiyu; He, Binbin; Mei, Yi; Zu, Yun (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
[Display omitted] •Migration regulation of Ca2+ species in the CaNaX zeolite was revealed in detail.•Utilization of hydroxylated Ca2+ species in the supercages of CaNaX zeolite was maximized via low-temperature calcination.•Remarkable CO2 uptakes and selectivity on the 0.05CaNaX-250 zeolite were achieved.•This new sorbent displayed low heat of adsorption, fast kinetics and superior recyclability.•The formation of Ca(OH)+∙∙∙(CO2)2 adducts revealed by CO2-dosing FTIR experiments. Ca-FAU zeolite sorbents have been recognized as one of promising CO2 capture materials, while it is subject to the change in the speciations and locations of Ca2+ species as adsorption sites in the FAU zeolite due to its susceptible migration. In this paper, a facile strategy is reported by tuning calcination temperatures and Ca loadings, to maximize the utilization of Ca2+ species in the supercages of CaNaX zeolites. Detail characterizations of TG-MS, in situ FTIR spectroscopy and XRD Rietveld refinement reveal the changeable regular in the chemical speciations, locations and number of Ca2+ species in the CaNaX zeolites. Synthetic 0.05CaNaX-250 zeolite (calcined at 250 °C and Ca loading of 1.58 wt%) guarantees at least 21 Ca(OH)+ species (depicted as hydroxylated Ca2+ species) in the supercages per FAU cell unit, close to theoretical value. Such sorbent apparently improves the CO2 uptakes and the separation from CO2/N2 and CO2/CH4, along with fast kinetics, low heat of adsorption, measured by dynamic and gravimetric adsorption methods, respectively. In addition, it keeps a superior recyclability after 10 times regeneration. CO2-dosing FTIR experiments further illustrate that excellent CO2 adsorption performance are benefited from the formation of Ca(OH)+∙∙∙(CO2)2 adducts with an appropriate interaction. This work is of great significance to better understand the role of cations in FAU zeolites, and also provides an important reference value for the directional design of effective adsorption sites in other excellent CO2 zeolite sorbents.